Southeast Australia encapsulates the recent decade of extreme global weather and climate events - Milton Speer; Lance Leslie (Academia Environmental Sciences and Sustainability)
Southeast Australia (SEAUS) is a microcosm of the worldwide impacts of accelerated global warming (GW) since 2010. SEAUS experienced record rainfall and floods in La Niña years 2010–2012, followed by extreme heat and drought in 2013–2019. Catastrophic bushfires occurred in 2019–2020. Next, during successive La Nina years 2020–2023, SEAUS endured record rainfall, floods, and unseasonably cool summers. Accelerated GW amplifies the impacts of SEAUS climate drivers, depending on their phases. We used machine learning attribution to identify climate drivers responsible for a range of extreme events. Attribute detection can provide early extreme event alerts for SEAUS urban and rural communities.